GPS observation of continent‐size traveling TEC pulsations at the start of geomagnetic storms. Issue 8 (27th August 2014) - Pradipta, R.; Valladares, C. E.; Doherty, P. H.
Abstract We report our experimental observation of continent‐size traveling plasma disturbances using GPS measurements of total electron content (TEC) over the North American sector. These plasma disturbances occurred at the beginning of geomagnetic storms, immediately after the shock arrived, and prior to the appearance of large‐scale traveling ionospheric disturbances (LSTIDs) from the auroral region. Specifically, these supersize TEC perturbations were observed when the interplanetary magnetic field Bz was oscillating between northward and southward directions. They were found to propagate zonally with a propagation speed of 2–3 km/s. We interpret these TEC pulsations as ion drift waves in the magnetosphere/plasmasphere that propagate azimuthally inside the GPS orbit.